G283 Epilepsy12 – united kingdom collaborative clinical audit of health care for children and young people with suspected epileptic seizures. (27th April 2015) - Down, C; Waldron, B; Maini, R; Williams, FLR; Brown, A; Notghi, L; Martin, K; Chin, R; Basu, H; Kirkpatrick, M; Ferrie, C; Whitehouse, WP; et al.
Abstract : Objective: To assess changes between 2012 and 2014 in the quality of paediatric clinical and nursing care for UK children and young people affected with seizures and epilepsies. Methods: Epilepsy12, a UK wide audit, commenced in 2009 with the aim of evaluating epilepsy care against NICE and SIGN guidelines. All NHS hospital and community paediatric services managing children with epilepsy were invited to participate. National key recommendations and local action plans were made after Round 1. Round 2 was undertaken between 2013 and 2014 to assess changes since Round 1 and results are reported here. Children referred for first EEG were used to find a new cohort of eligible children aged 1 month to 16 years receiving a first paediatric assessment between January and April 2013 for afebrile paroxysmal episodes. Retrospective case-note analysis was undertaken using a specifically designed web-based platform and audit pack. Service descriptor data were collected from secondary services on census day, 1 January 2014. Patient reported experience measure (PREM) questionnaires were collected from sequential children with epilepsy and their carers/parents attending clinics between February and March 2014. Results: 192/196 paediatric services enrolled. 186 units provided service descriptor data, 174 clinical audit data and 145 PREM data. The clinical cohort consisted of 3449 patients; median age 5.2 years; male: female 55:45%. Anonymised PREM data were received from 2335 parents, carers, children and young people. 45% of first assessments occurred within an acute presentation. 35% of children had epilepsy diagnosed by 12 months. 22.6% of children had a documented neurodisability. 68% of paediatric services now have at least one Epilepsy Specialist Nurse (ESN). There has been a significant increase in percentage of children having ESN input; access to a paediatrician with expertise in epilepsies; appropriate assessment, classification and investigations in 2014 compared to 2012. PREM data showed 88% (1897/2148) overall satisfaction with services; 20% thought that staff are not good at working together. Conclusion: There is evidence of significant improvements in the provision of medical and nursing epilepsy care. However, many children still do not receive recommended practice and access fully resourced paediatric epilepsy services.